2016
DOI: 10.1099/ijsem.0.001209
|View full text |Cite
|
Sign up to set email alerts
|

Aquimarina aggregata sp. nov., isolated from seawater

Abstract: A novel Gram-stain-negative, agarolytic, rod-shaped, non-flagellated, strictly aerobic strain with gliding motility, designated RZW4-3-2 T , was isolated from coastal seawater of the Yellow Sea in China (119.625 E 35.517 N). The organism grew optimally at 28 C, at pH 7.0 and in the presence of 2.0-3.0 % (w/v) NaCl. The strain required seawater or artificial seawater for growth, and NaCl alone did not support growth. Strain RZW4-3-2 T contained MK-6 as the major respiratory quinone and iso-C 17 : 0 3-OH, iso-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The genus Aquimarina is a Gram-negative, aerobic, halophilic microorganism and affiliated with the phylum Bacteroidota (formerly Bacteroidetes ) and the family Flavobacteriaceae. They are normally found in marine environments ( Hahnke and Harder, 2013 ; Wang et al, 2016 , 2018 ), as well as in various marine hosts such as algae, sponges, and lobsters ( Kennedy et al, 2014 ; Kumar et al, 2016 ; Ranson et al, 2018 ). However, some Aquimarina species contain type 9 secretion system, gliding motility apparatus, and enzymes such as chitinase that breaks down crude chitin ( Hudson et al, 2019 ; Silva et al, 2019 ), which may contribute to development of ESD in lobsters.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Aquimarina is a Gram-negative, aerobic, halophilic microorganism and affiliated with the phylum Bacteroidota (formerly Bacteroidetes ) and the family Flavobacteriaceae. They are normally found in marine environments ( Hahnke and Harder, 2013 ; Wang et al, 2016 , 2018 ), as well as in various marine hosts such as algae, sponges, and lobsters ( Kennedy et al, 2014 ; Kumar et al, 2016 ; Ranson et al, 2018 ). However, some Aquimarina species contain type 9 secretion system, gliding motility apparatus, and enzymes such as chitinase that breaks down crude chitin ( Hudson et al, 2019 ; Silva et al, 2019 ), which may contribute to development of ESD in lobsters.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, it was thought that the glycine hinge was absolutely conserved, rendering this pivot point the universal hinge in H‐NOX proteins. However, continued genome searching revealed that several Flavobacteriaceae have H‐NOXs with native alanine substitutions in one of the glycine hinge residues (Figure B). These H‐NOXs provided an opportunity to directly interrogate the effect of steric bulk in the hinge region.…”
Section: The Glycine Hinge Region Determines Flexibility Between the mentioning
confidence: 99%
“…For instance, Aquimarina salinaria (Chen et al, 2012) was shown to possess antagonistic activity towards the toxic cyanobacterium Microcystis aeruginosa (Chen et al, 2011;Chen et al, 2012). Furthermore, at least three Aquimarina species have already been described to possess agarolytic activity, namely, A. aggregata, A. agarivorans and A. agarilytica (Lin et al, 2012;Zhou et al, 2015;Wang et al, 2016). Aquimarina species have as well been implicated in the emergence of epizootic shell disease (ESD) in the American lobster (Homarus americanus).…”
Section: Introductionmentioning
confidence: 99%